PERANCANGAN DAN PEMBUATAN SISTEM PENEBAR PAKAN IKAN JENIS PASTA OTOMATIS BERBASIS MIKROKONTROLER AT89S51 - Ariyanto, Eko Yanu; Aman, Mujahid; Rochmad, Catur Diah (Program Kreativitas Mahasiswa - Karsa Cipta, 2013)
Indonesia is an agricultural country with abundant natural resources, including fishery. Fishermen are found almost throughout parts of Indonesia with different size pool or pond. Manually feeding is ineffective because of the number of fishâs food used was not always fixed even if it takes a long time feeding evenly throughout the pool. Spreader tool forage fish species AT89S51 microcontroller-based pasta has been made to provide the feed of pasta with fixed volumes levelled DC motor based machine.